Risk of Cardiovascular Disease Due to General Anesthesia and Neuraxial Anesthesia in Lower-Limb Fracture Patients: A Retrospective Population-Based Cohort Study - Yeh, Han-Wei (Int J Environ Res Public Health, 2019)
The purpose of this study was to analyze the relationship between elevated cardiovascular disease (CVD) risk and type of anesthesia by using the National Health Insurance Research Database (NHIRD) of Taiwan in a one-year follow-up period. We assessed whether general anesthesia (GA) or neuraxial anesthesia (NA) increased CVD occurrence in lower-limb fracture patients. Approximately 1 million patients were randomly sampled from the NHIRD registry. We identified and enrolled 3437 lower-limb fracture patients who had received anesthesia during operations conducted in the period from 2010 to 2012. Next, patients were divided into two groups, namely GA (n = 1504) and NA (n = 1933), based on the anesthetic technique received during surgery. Our results revealed that those receiving GA did not differ in their risk of CVD relative to those receiving NA, adjusted HR = 1.24 (95% CI: 0.80–1.92). Patients who received GA for more than 2 h also did not differ in their risk of CVD relative to those receiving NA for less than 2 h, adjusted HR = 1.43 (95% CI: 0.81–2.50). Moreover, in the GA group (i.e., patients aged ≥65 years and women), no significant difference for the risk of CVD events was observed. In conclusion, in our study, the difference in the risk of CVD between lower-limb fracture patients receiving NA and GA was not statistically significant. The incidence rate of CVD seemed to be more correlated with patients’ underlying characteristics such as old age, comorbidities, or admission to the intensive care unit. Due to the limited sample size in this study, a database which reviews a whole national population will be required to verify our results in the future.